A multi-agent optimal operation methodology of electric, thermal, and hydrogen integrated energy system based on ADMM algorithm - Zhou, Dongxu; Xu, Jingzhou; Zhang, Can; Wei, Pengchao; Pan, Guangsheng; Gu, Zhongfan (Frontiers in Energy Research, 2024)
This article presents a study on the distributed optimization operation method for micro-energy grid clusters within an electric, thermal, and hydrogen integrated energy system. The research focuses on precisely modeling the Power-to-Hydrogen (P2H) conversion process in electrolytic cells by considering their startup characteristics. An optimization operation model is established, with each micro-energy grid as the principal entity, to cater to their individual interests and demands. The Alternating Direction Method of Multipliers (ADMM) algorithm is adopted for distributed solution.Case studies demonstrate that the connection topology between micro-energy grids significantly impacts the total operating cost, and the effectiveness of the ADMM algorithm is validated through a comparison with centralized optimization approaches.